The NANOGrav 15 yr Data Set: Search for Gravitational-wave Memory - Gabriella Agazie; Akash Anumarlapudi; Anne M. Archibald; Zaven Arzoumanian; Jeremy G. Baier; Paul T. Baker; Bence Bécsy; Laura Blecha; Adam Brazier; Paul R. Brook; Sarah Burke-Spolaor; Rand Burnette; et al. (The Astrophysical Journal, 2025)
We present the results of a search for nonlinear gravitational-wave (GW) memory in the NANOGrav 15 yr data set. We find no significant evidence for memory signals in the data set, with a maximum Bayes factor of 3.1 in favor of a model including memory. We therefore place upper limits on the strain of potential GW memory events as a function of sky location and observing epoch. We find upper limits that are not always more constraining than previous NANOGrav results. We show that it is likely due to the increase in common red noise between the 12.5 and 15 yr NANOGrav data sets.